LESSONS OF LOVE IN ACHILLES TATIUS: COMMENTARY, TRANSLATION AND NOTES BY LEUCIPPE AND CLITOPHON I.7-15. - Cerdas, Emerson (Revista Archai, 2025)
We presente the trnaslation of a specific passage from the novel Leucippe and Clitophon, by Achilles Tatius: the scene in which the main character goes to meet his cousin Clinias and receives from him valuable teachings on seduction. This passage draws our attention because it dialogues with Roman erotic elegy, especially Ovid's Ars Amatoria, and because of its concise, unitary structure, which resonates like a short story within the novel. We have sought to recreate in our translation aesthetic and literary elements that resonate with these elements, especially the dynamism of the narrative, without losing the lyrical - or elegiac - nuances of the text.